A management and visualization framework for reconfigurable WDM optical networks. - Liu, K.H.
As the phenomenal advance in optical WDM networking technologies continues, optical WDM network equipment has been deployed not only in backbone networks, but also in regional, metropolitan, and access networks. It is widely believed that a major component of the next-generation Internet will be an IP-based optical network employing WDM. WDM wavelength routing and signaling have become an active research field, and dynamic and adaptive wavelength routing and assignment algorithms have been proposed. However, there is less work on reporting network control and management system implementation efforts over testbed WDM networks. This article presents a network management and visualization framework aimed at guiding the development of management applications for reconfigurable WDM optical networks. A layered framework architecture including element and network management and visualization is provided, and an object-based information model representing the WDM network is introduced. Functional components on reconfiguration, software agent, and network visualization services are presented, and important issues related to optical lightpath generation are discussed. A network visualization service also provides WDM control and management APIs to applications and access networks such as an IP network management system. To illustrate the usage of the framework, we share our experience in implementing the MONET network control and management system, and present network visualization views obtained from the MONET WDM network to highlight the framework features.
Keywords: API; IP network management system; IP-based optical network; Internet; MONET WDM network; MONET network control system; MONET network management system; Access networks; Adaptive wavelength routing; Backbone networks; Dynamic wavelength routing; Element management; Element visualization; Layered framework architecture; Metropolitan networks; Network visualization services; Object-based information model; Optical WDM network equipment; Optical lightpath generation; Reconfigurable WDM optical networks; Regional networks; Software agent; Testbed WDM networks; Wavelength assignment algorithms; Wavelength routing algorithms; Wavelength signaling